An analysis of the link between individual identity traits and radical party choice. Issue 5 (20th October 2021) - Filip, Alexandru; Lorenz, Jan
ABSTRACT: While recent trends in the study of radical party voting have tended to focus on egalitarian attitudes and individual personality traits in their endeavour to explain radical party choice, the present study pits individual identity traits in the spotlight of ballot box behaviour, using data from the World Values Survey and European Values Survey. We analyse the link between exclusive and inclusive identity (identifying with a more restricted 'in-group' versus identifying with a larger community) and the propensity to vote for radical right and radical left parties, using differences in individual identification with respondents' home nation and as European citizens. The results show that exclusive individual identity is a good predictor of radical right party choice, even in the presence of redistributive and egalitarian values usually associated with left-wing voting. The results also speak to the literature on welfare chauvinism. While the presence of strong egalitarian and redistributive attitudes does indeed normally predict radical left party preference in line with previous findings, this relationship is complicated by the presence of exclusive individual identity, which moderates the former's effect and can induce egalitarian voters to prefer radical right parties. In conclusion, the paper explores the interaction of identity and social class.